Can mobile eco-systems for technical innovations be standardized? The case of mobile wallets and contactless communication - Jan Markendahl; Per Andersson; Lars-Gunnar Mattsson (International Telecommunications Society (ITS), 2011)
This paper puts focus on the application of Near Field Communication technology (NFC) to mobile payments. Uncertainties about global policies open for a variety of local business policies. Taking into account different representations of actor interaction as described by different eco-systems by different policy forums the main research question to be discussed in the paper is: Can policies or standards describing actor roles and responsibilities for technical innovations like mobile payments remove obstacles for introduction of the innovation? Different types of industry forums are not only involved in strictly technical matters but also discuss and describe visions about how a new technique might be applied in business life. They suggest different business architectures, (not only a technical architecture), where roles of different type of actors and relations between actors are outlined based on ideas about so called eco-systems. Against this background the paper first discusses how NFC enabled mobile payments currently attracts a lot of attention and identifies four possible development paths making it happen. The paper discusses and compares how global policy networks describe the technical and business architectures for mobile payments. The paper uses a business practice analytical framework and an industrial network framework to identify major problems in connecting global and local policies. Some comments on further research finalize the paper.
Keywords: L52; L96; M16; O19; O32; 330; Near Field Communication; mobile payments; global policy; business architecture; policy forum; industrial networks; practice